RANCANGAN TEKNIS PENAMBANGAN BATUANDESIT DI CV. HANDIKA KARYA KABUPATEN KULON PROGO DIY - Juni Triyono; Waterman Sulistyana; Untung Sukamto; Suyono Suyono (Jurnal Teknologi Pertambangan, 2016)
CV. Handika Karya is one of the mining companies of andesite quarry, located in the Hargorejo village and Kalirejo village, Kokap, Kulon Progo, Special Region of Yogyakarta. CV. Handika Karya has a production plan from the first until the seventh year of andesite 120.000 bcm/year or 330.000 tones/year. CV. Handika Karya has 63,72 hectares of IUP area.The identified problem of this research is CV. Handika Karya needs a mine design for andesite mining production plan. The problem-solving method is done by processing secondary data which is processing topographic map to build the mine design and to estimate the andesite reserve.Based on pit bottom limit plan and ultimate quarry slope, it is found that the reserve is 4,719,612 bcm or 12,978,933 tons. Mining slope geometry of bench high is 5 m, bench width is 5 m, single slope is 90o, and overall slope is 48o. The width of the straight road is 7 m, the width of the curved road is 11 m, the value of the minimum corner road radius is 6 m, cross slope 30 mm/m, super elevation is 0.44 m of the curved road width and 10% maximum grade of hauling road. The obtained result of andesite production scheduling in the study area is 337,040 tons on the first year, 337,145 tons on the second year, 336,970 tons on the third year, 337,185 tons on the fourth year, 336,918 tons on the fifth year, 337,078 tons on the sixth year, and 336,893 tons on the seventh year. There is no addition of the unit of the loader in the need of mechanical equipment for mining activities, whereas the unit of the haulers has increased. This happened due to the effectiveness of work equipment decreases in every year. Mine equipment that is used in CV. Handika Karya are Excavator CAT 336D loader for 1 unit and DT Mitsubishi Colt diesel hd 125ps haulers for 27 units.Keywords : andesite, estimate,desain, mechanical utility ABSTRAKCV. Handika Karya merupakan salah satu perusahaan yang melakukan penambangan batuandesit terletak di Desa Hargorejo dan Desa Kalirejo, Kecamatan Kokap, Kabupaten Kulon Progo, Provinsi Daerah Istimewa Yogyakarta. CV. Handika Karya mempunyai rencana produksi penambangan tahun pertama hingga tahun ketujuh sebesar 120.000 bcm atau 330.000 ton per tahun. Luas IUP Opersai Produksi adalah 63,72 hektar.Permasalahan pada penelitian ini adalah CV. Handika Karya belum melakukan perancangan penambangan untuk rencana produksi batuandesit. Metode penyelesaian masalah dilakukan dengan pengolahan data sekunder.Berdasarkan batas lantai dasar penambangan yang direncanakan dan batas terluar penambangan, diketahui cadangan tertambang sebesar 4.719.612 bcm atau 12.978.933 ton. Geometri lereng penambangan untuk bench high adalah 5 m, bench width 5 m, single slope 90o, dan overall slope 48o. Lebar pada jalan lurus adalah 7 m, lebar jalan pada tikungan 11 m, nilai radius tikungan jalan minimum 6 m, beda tinggi kemiringan melintang 0,105 m dari cross slope 30 mm/m, super elevasi sebesar 0,44 m, dan kemiringan jalan angkut yang digunakan maksimal 10 %. Hasil yang diperoleh untuk penjadwalan produksi batuandesit pada daerah penelitian pada 7 tahun pertama sebesar 337.040 ton pada tahun pertama, 337.145 ton pada tahun kedua, 336.970 ton pada tahun ketiga, 337.185 ton pada tahun keempat, 336.918 ton pada tahun kelima, 337.078 ton pada tahun keenam, dan 336.893 ton pada tahun ketujuh.   Kebutuhan  alat mekanis selama kegiatan penambangan tidak mengalami penambahan unit untuk alat muat, sedangkan untuk alat angkut mengalami penambahan unit. Hal ini disebabkan karena efektifitas kerja alat berkurang setiap tahunnya. Alat muat yang digunakan di CV. Handika Karya Excavator CAT 336D berjumlah 1 unit dan alat angkut DT Mitsubishi Colt diesel hd 125ps berjumlah 27 unit.Kata kunci : batuandesit, penaksiran, pancangan, peralatan